2017
DOI: 10.1124/dmd.117.076554
|View full text |Cite
|
Sign up to set email alerts
|

Organic Cation Transporter 1 Is Responsible for Hepatocellular Uptake of the Tyrosine Kinase Inhibitor Pazopanib

Abstract: Pazopanib is an orally active tyrosine kinase inhibitor that exhibits hepatotoxicity in some patients. Despite the clinical importance of its hepatic distribution, the transporter(s) responsible for hepatic uptake of pazopanib in humans remain undetermined. To characterize its hepatic uptake mechanism, we screened the effects of several transporter inhibitors, including tetrapentylammonium (TPeA) for organic cation transporters (OCTs) and cyclosporin A (CsA) for organic anion-transporting polypeptides (OATPs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…These TKIs may be transported into hepatocytes by these solute carriers. Our recent in vitro and in vivo experiments have revealed that pazopanib is a substrate of the human organic cation transporter 1 [53].…”
Section: Pharmacokinetic Properties Of Anticancer Drugs Mainly Eliminmentioning
confidence: 99%
“…These TKIs may be transported into hepatocytes by these solute carriers. Our recent in vitro and in vivo experiments have revealed that pazopanib is a substrate of the human organic cation transporter 1 [53].…”
Section: Pharmacokinetic Properties Of Anticancer Drugs Mainly Eliminmentioning
confidence: 99%
“…Several tyrosine kinase 250 inhibitors (TKIs, which are small molecules used to treat various forms of cancer) are substrates 251 and/or inhibitors of OATPs. Pazopanib has a boxed warning for hepatotoxicity in the US FDA 252 label, but the mechanism of hepatotoxicity is not related to inhibition of OATP1B1 40 ; pazopanib 253 uptake is mediated by the organic cation transporter 1 (OCT1, encoded by SLC22A1) 41 . The FDA 254 provides further guidance on in vitro metabolism-mediated and transporter-mediated drug-255 drug interaction studies with investigational drugs 42 .…”
mentioning
confidence: 99%
“…To evaluate the tissue distribution of OATP1B endogenous substrates, tissue-to-plasma concentration ratio (K p,tissue ) was calculated by dividing the amount of OATP1B endogenous substrates per gram of tissue by their plasma concentration at 2 h after RSV administration. 22 To perform renal ligation, fasted rats were anesthetized with isoflurane, and the renal vein and artery of bilateral kidneys were ligated with surgical thread (Natsume). After bilateral kidneys were resected, the abdominal muscle was sutured to close the wound.…”
Section: Pharmacokinetic Studies In Ratsmentioning
confidence: 99%
“…Briefly, hepatocytes were pre-incubated for 10 min at 37 C with KH buffer, and then the buffer was changed to a dosing solution of pre-warmed KH buffer containing substrate (d-HDA) with or without inhibitors (PBD, RIF, and CsA), and in the presence of 10 mM fatty acid-free human serum albumin (HSA; Sigma-Aldrich, St. Louis, MO). 22,25 After 30 min, the dosing solution was immediately removed, and cells were rinsed three times with ice-cold KH buffer. Transport studies involving RSV and PTV were performed using the same methodology but without HSA, and the incubation duration was set at 2 min.…”
Section: Transport Studies In Isolated Rat Hepatocytesmentioning
confidence: 99%